Students’ perception on the Digital Storytelling implementation on Developing the Writing Skills - Sektalonir Oscarini Wati Bhakti (Jurnal Bahasa Inggris Terapan, 2020)
This research tried to explore Civil Engineering students’ perception on the impact of Digital Storytelling strategy on developing the students’ writing skills. There were 48 participants from two classes in Civil Engineering Department in Politeknik Negeri Samarinda filled out the adopted questionnaires. The questionnaire was asked divided into two sections. The sections were the students’ perspective regarding the digital storytelling and the students’ writing. The results showed that 85% of the students agreed that Digital Storytelling helped them in the process of learning in the class. They found out that this strategy made them enjoy the class. And, whilst 88% of the participants agreed that the digital storytelling helped them to write well since they know the elements of writing. The keyword: Perception, digital storytelling, writing skills